Answer:
f^-1(x) = The quantity of 3x plus 2, divided by 4.
Step-by-step explanation:
Given: f(x) = (4x -2)/3
Which is y = (4x - 2)/3
We have to find the inverse function f^-1 (x)
Replace x by y and y by x, we get
x = (4y - 2)/3
Now find the function y interms of x.
3x = 4y - 2
4y = 3x + 2
y = (3x + 2)/4
f^-1(x) = The quantity of 3x + 2, divided by 4.
Answer is D) f^-1(x) = The quantity of 3x plus 2, divided by 4.
Hope this will helpful.
Thank you.
Answer:
Area of a rectangle equals length x width soooo
The side lengths should be 2 and 8 since they are what equals 16
Answer:-5
Step-by-step explanation:
The answer is 18
-7^2+4(-7)-3
49+(-28)-3
21-3
18
Answer:
10 ![10\frac{5}{8}](https://tex.z-dn.net/?f=10%5Cfrac%7B5%7D%7B8%7D)
Step-by-step
Reduce
to
and simply subtract.